Cutibacterium and Staphylococcus dysbiosis of the skin microbiome in acne and its decline after isotretinoin treatment - Cecilie Feidenhansl; Michael Lund; Anja Poehlein; Rolf Lood; Hans B. Lomholt; Holger Brüggemann (Wiley, 2024)
Abstract Background Acne vulgaris is a multifactorial disease of the pilosebaceous unit of human skin. Previous studies have identified an acne‐associated dysbiosis of the skin microbiome. Objectives This dysbiosis was mainly determined for Cutibacterium acnes. However, detailed analyses combining qualitative and quantitative aspects are scarce, also regarding the possible contribution of other skin bacteria and the impact of treatment. Methods We conducted a culture‐independent study to determine differences between the healthy skin and the acne microbiome before and after isotretinoin treatment. Three amplicon‐based sequencing approaches and digital droplet PCR for quantification were applied. Results Our results revealed a 2.2‐fold reduced abundance of C. acnes with a reduced diversity in the acne microbiome. A phylotype switch was found, which was mainly characterized by a significant relative decrease of IB and II strains in the acne microbiome. In contrast, the relative abundance of staphylococci increased significantly and the quantitative ratio of staphylococci to C. acnes strongly increased from 1:34 in the healthy cohort to 1:11 in the acne cohort. The diversity of staphylococci was reduced, mainly due to the decrease of Staphylococcus hominis, and the appearance and predominance of Staphylococcus aureus in some acne patients. Isotretinoin treatment drastically depleted C. acnes (37‐fold) and moderately also staphylococci (3.6‐fold). Isotretinoin treatment resulted in a decrease of Staphylococcus epidermidis and a significant increase of S. aureus on facial skin. Conclusions The switch from a C. acnes‐dominated healthy skin microbiome towards an acne microbiome that is relatively enriched in staphylococci could indicate a stronger impact of staphylococci in the pathophysiology of acne than currently acknowledged. Our data further showed that isotretinoin largely eliminated the skin microbiome and in particular C. acnes, but also S. epidermidis. Instead, more harmful bacteria such as S. aureus could expand, suggesting that posttreatment strategies should be considered to accelerate skin microbiome recovery.